KOMBINASI MEDIA TANAM DAN PEMBERIAN BERBAGAI DOSIS PUPUK GROW QUICK LB TERHADAP PERTUMBUHAN ANGGREK DENDROBIUM (Dendrobium sp.) PASCA AKLIMATISASI - Nofripa Herlina; Novia Gesriantuti; Anis Restiawati (Sistem Informasi, 2017)
Dendrobium orchid is one of the very popular ornamental plant because of the flower is beautiful and has a high economic value. An effort to prevent the orchid from extinetion is by means of in vitro propagation. The study aims to look at the effect of various doses of fertilizers Grow Quick LB and types of growing media and their interaction on the growth of Dendrobium sp. post acclimatization.The completely randomized design was used with two factors. The firs factor was type medium (charcoal+fern, charcoal+cocopeat), the second factor was type of Grow Quick LB fertilizer (0ml/L, 1ml/L, 2ml/L, 3ml/L). Parameters observed were, plantlet height, leaf length, leaf width, and number of leaves. The results showed that the dosing of Grow Quick LB fertilizer 1ml/L showed the highest values for the parameters width of leaves and number of leaves, whereas a dose of 2ml/L showed the highest values for the parameters plantlet height, leaf length. A combination of types of growing media charcoal+cocopeat showed a better effect than the media charcoal+fern on all parameters. The interaction of medium type and Grow Quick LB fertilizer significantly different with plantlet height and leaf length and not significantly different with parameters leaf width, and number of leaves.